2022
DOI: 10.3390/jcm11175238
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Laboratory Diagnostics of Primary Biliary Cholangitis: When Solid-Phase Assays and Immunofluorescence Combine

Abstract: The laboratory diagnostics of primary biliary cholangitis (PBC) have substantially improved, thanks to innovative analytical opportunities, such as enzyme-linked immunosorbent assays (ELISA) and multiple immunodot liver profile tests, based on recombinant or purified antigens. This study aimed to identify the best diagnostic test combination to optimize PBC diagnosis. Between January 2014 and March 2017, 164 PBC patients were recruited at the hospitals of Parma, Modena, Reggio-Emilia, and Piacenza. Antinuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 29 publications
0
10
0
2
Order By: Relevance
“…7,8 Some studies have shown that nearly 30% to 50% of PBC patients are positive for anti-gp210 and anti-sp100 antibodies. 9,10 At present, immunoblotting assay (IBT) is widely used method to detect autoantibodies in China. IBT has some disadvantages of being cumbersome and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Some studies have shown that nearly 30% to 50% of PBC patients are positive for anti-gp210 and anti-sp100 antibodies. 9,10 At present, immunoblotting assay (IBT) is widely used method to detect autoantibodies in China. IBT has some disadvantages of being cumbersome and timeconsuming.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, antinuclear antibodies (ANA) are present in part of PBC patients, especially nuclear envelope antibody (anti‐gp210 antibody) and multiple nuclear dots (anti‐sp100 antibody) 7,8 . Some studies have shown that nearly 30% to 50% of PBC patients are positive for anti‐gp210 and anti‐sp100 antibodies 9,10 …”
Section: Introductionmentioning
confidence: 99%
“…Primary biliary cholangitis (PBC) is a chronic autoimmune liver disorder characterized by inflammation of intrahepatic biliary ducts, which leads to fibrosis and consequently may produce cirrhosis and liver failure [1][2][3][4][5]. Its prevalence is low and it mostly affects middle-aged women [1,6].…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence is low and it mostly affects middle-aged women [1,6]. The etiology is unclear, but many data suggest that a genetic predisposition along with environmental risk factors such as infections or smoking may be a crucial responsible [1,4]. Clinical presentation is variable, and patients range from asymptomatic and stable or slowly progressive to symptomatic and rapidly progressive [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation